Manajemen Jalan Nafas pada Pasien dengan Sindroma Crouzon - Sari, Djayanti; Widyastuti, Yunita; Hidayat, Fachsyar (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Crouzon syndrome is a congenital disorder that prevents premature closure of the coronal suture (synostosis), or, less commonly, the sagittal or lambdoidal suture of the cranium. This results in a skull dysmorphic appearance of the skull and face, with a high forehead, flattened occiput, and brachycephaly. Inaddition to craniosynostosis, affected children may also experience an abnormal fusion of the skull base and central bones, resulting in maxillary hypoplasia, high arched palate, and shallow orbits, causing protruding exophthalmos. These abnormalities in facial features can have implications for managing a difficult airway. A 4-year-old woman with a head complaint from the age of 1 year. The patient has a history of being diagnosed with Crouzon syndrome